Gamma knife surgery for pineal region tumors: an alternative strategy for negative pathology - Peng Wang; Qing Mao; Wei Wang; Liang-Xue Zhou; Yan-Hui Liu (Arquivos de Neuro-Psiquiatria)
Objective : Pineal region tumors (PRTs) are uncommon, and treatments vary among neoplasm types. The authors report their experience with gamma knife surgery (GKS) as an initial treatment in a series of PRT patients with unclear pathological diagnoses. Method : Seventeen PRT patients with negative pathology who underwent GKS were retrospectively studied. Nine patients had further whole-brain and spinal cord radiotherapy and chemotherapy 6–9 months after GKS. Results : Sixteen of 17 cases were followed up over a mean of 33.3 months. The total response rate was 75%, and the control rate was 81.3%. No obvious neurological deficits or complications were attributable to GKS. Conclusion : The findings indicate that GKS may be an alternative strategy in selected PRT patients who have negative pathological diagnoses, and that good outcomes and quality of life can be obtained with few complications.